Info Plástica UNIFESP: aplicativo sobre cirurgias plásticas mais realizadas no Brasil - Carvalho Júnior, José da Conceição [UNIFESP] (2016)
Introduction: The number of plastic surgery increases every year. Brazil is the deputy leader in the ranking second only to the US. This leads to a huge audience with an interest in information about these procedures. The internet presents itself as the primary means to search for answers and most people accessing this source through smartphones. Objective: To develop an app for smartphones with information about plastic surgery most performed in Brazil. Methods: The five most performed surgeries in Brazil were selected, according to the ISAPS (International Society of Plastic Surgery Aesthtic) which are liposuction, breast augmentation, blefaroplasty, tummy tuk and rinoplasty. For assembling the content we used information contained in the book Clinic and Hospital Medicine Guide UNIFESP - Plastic Surgery, on the site of the Brazilian Society of Plastic Surgery (SBCP), the American Society of Plastic Surgeons (ASPS) and the American Society of Aesthetic and Plastic Surgery (ASAPS). You Tube videos with testimonials postoperative patients were used for better understanding of the real questions of patients. For better readability of printed texts, they were distributed to public patients. All content has been reviewed and in the end the material was delivered to a firm to produce software app. Results: Each of the five surgeries had their content presented in the app with the following items: What is it? Who are the candidates? Preparations for surgery; Steps surgery; Post surgery recovery; Complications; Choose your surgeon; Consult; What is the cost? and Glossary. The result was the creation of an app with extensive content about plastic surgery most performed in Brazil in which the user can take much of your questions regarding the various aspects involved in these procedures. Conclusion: Info Plástica UNIFESP is presented as a source of information about plastic surgery and is available in a practical, accessible and free for smartphones.